Bacterial Succession in Microbial Biofilm as a Potential Indicator for Postmortem Submersion Interval Estimation - Dmitrijs, Finkelbergs; Guo, Juanjuan; Huang, Yecao; Liu, Yafei; Fang, Xinyue; Jiang, Kankan; Zha, Lagabaiyila; Cai, Jifeng; Fu, Xiaoliang (Frontiers in Microbiology, 2022)
Bacteria plays as the main decomposer of the microbial communities during the process of biodegradation in the ecosystem. Numerous studies have revealed the bacterial succession patterns during terrestrial carcass decomposition. The machine learning algorithm-generated models based on such temporal succession patterns have been developed for estimating the postmortem interval (PMI). However, up to now, the bacterial succession occurs on decomposing carcasses in the aquatic environments are poorly understood. In forensic practices, the postmortem submersion interval (PMSI), which approximately equals PMI in most common drowning cases, has long been problematic to determine. In present study, the bacterial successions in the epinecrotic biofilms formed on submerged swine carcasses were analyzed by sequencing the variable region 4 (V4) of 16S rDNA. The succession patterns between the repeated experimental settings were repeatable. Using the machine learning algorithm for establishing random forest (RF) models, the community succession patterns in the epinecrotic biofilms during the 56 d winter trial and 21 d summer trial were determined to predict PMSI with the mean absolute error (MAE) of 17.87 ± 2.48 ADD (≈ 1.3 d) and 20.59 ± 4.89 ADD (≈ 0.7 d), respectively. While, significant differences were observed between the seasons and between the substrates. The presented data suggested that the influences of environmental factors and the aquatic bacterioplankton on succession patterns of biofilm bacteria were of great significant. The related mechanisms need to be clarified in depth when consider epinecrotic biofilm as a reliable predictor in forensic investigations.